Deep Cervical Abscess Associated with Internal Carotid Pseudoaneurysm and Acute Ischemic Stroke: a case report - dos Santos Ferreira, Ingrid; Knorst Kepler, Carolina; Travi Dornelles , Nicholas; Schüler Nin , Carlos (Brazilian Journal of Case Reports, 2022)
The formation of an internal carotid pseudoaneurysm is a rare complication of upper airway infections, mainly after the advent of antibiotic therapy. Despite the low incidence of this condition, it is an extremely serious and potentially lethal scenario; therefore, the rapid identification and establishment of an effective therapy is vital to patient. Normally, the proposed treatment is an immediate open ligature of the involved artery. Currently, new endovascular techniques have been used in the treatment of this pathology. Unfortunately, even after the establishment of adequate measures in order to contain hemorrhages, many cases evolve to cerebral ischemia, besides other complications. The present study reports the case of a four-year-old boy who presented with a right parapharyngeal abscess, which developed into an internal carotid pseudoaneurysm, treated with embolization. Regardless of the treatment, the patient had an unfavorable evolution, in which he had disease progression with fistula, hemorrhage and consequent acute ischemic stroke (AIS).